2009
DOI: 10.2217/clp.09.8
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic potential of skeletal muscle satellite cells

Abstract: Lipases are acyl hydrolases that represent a diverse group of enzymes present in organisms ranging from prokaryotes to humans. This article focuses on an evolutionarily related family of extracellular lipases that include lipoprotein lipase, hepatic lipase and endothelial lipase. As newly synthesized proteins, these lipases undergo a series of co- and post-translational maturation steps occurring in the endoplasmic reticulum, including glycosylation and glycan processing, and protein folding and subunit assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 204 publications
1
23
0
1
Order By: Relevance
“…Thus, our findings may have therapeutic implications. Recent discovery of LMF1, GPIHBP1 and ANGPTL4 have provided key insights into LPL biology, where they play key roles at different stages of LPL maturation and function (Dijk and Kersten, 2014; Doolittle and Peterfy, 2010; Wang and Eckel, 2009). In this study, we have identified Sel1L as a modulator of LPL secretion from the ER.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, our findings may have therapeutic implications. Recent discovery of LMF1, GPIHBP1 and ANGPTL4 have provided key insights into LPL biology, where they play key roles at different stages of LPL maturation and function (Dijk and Kersten, 2014; Doolittle and Peterfy, 2010; Wang and Eckel, 2009). In this study, we have identified Sel1L as a modulator of LPL secretion from the ER.…”
Section: Discussionmentioning
confidence: 99%
“…LPL-mediated hydrolysis of dietary triglycerides packaged in chylomicrons is increased at adipose tissues during feeding (to increase lipid storage), but suppressed during fasting (Williams, 2008). Production of active LPL is tightly regulated at multiple stages (Dijk and Kersten, 2014; Doolittle and Peterfy, 2010; Wang and Eckel, 2009), one of which is in the ER. Various ER chaperones are required for the folding of nascent LPL polypeptides into properly folded dimeric state (Ben-Zeev et al, 1992; Ben-Zeev et al, 2002; Vannier and Ailhaud, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPL is generally thought to be a head-to-tail homodimer [4244]; consequently, one might reasonably presume that LPL would have two binding sites for GPIHBP1. Thus far, however, no one has shown that this is the case.…”
Section: Gpihbp1–lpl Interactionsmentioning
confidence: 99%
“…5 SCs represent a heterogeneous stem-cell population, 6,7 characterized by plasticity [8][9][10] and self-renewal. 11,12 Although SCs are mostly considered as myogenic precursors, they also undergo adipogenic differentiation induced by adipogenic factors 8,9,13,14 and by spontaneous occurrence; 8,10 this ability is greater in SCs from oxidative muscles than in those from glycolytic muscles 15 and it is increased in SCs isolated from 23-month-old mice compared with 8-month-old mice. 16 Moreover, it is likely that the SC's fate could be influenced by pathological conditions, such as obesity and diabetes.…”
Section: Introductionmentioning
confidence: 99%